Development of butter fermented with kefir: probiotic properties and sensory acceptance - Jessica Isabel Vellido; Natalia Portes Thiago Pereira; Andrea Carvalheiro Guerra Matias; Isabela Rosier Olimpio Pereira (O Mundo da Saúde)
Kefir is a fermented milk product obtained through gelatinous grains containing probiotic microorganisms, known for millennia worldwide due to its numerous benefits. Fermented foods, such as kefir, have been widely recognized for their health-promoting properties, including anti-inflammatory, antioxidant, and antimicrobial activities, as well as their ability to modulate the gut microbiota—factors that contribute to the prevention of chronic diseases and the promotion of overall well-being. The aim of this study was to develop a butter with probiotic properties by fermenting cream with kefir and to evaluate its acceptance. After cream fermentation with kefir, butter was obtained through the churning process. Yield, moisture content, titratable acidity, lactic acid bacteria (LAB) count, and yeast count were assessed. Product acceptance was evaluated by sensory analysis using a 9-point hedonic scale and a 5-point purchase intent scale, and results were compared to a commercial butter brand considered as the standard. Sensory analysis was carried out for each butter sample (kefir and standard) on different days. The kefir butter showed higher moisture and acidity levels compared to the standard. The LAB and yeast counts were approximately 10⁷ and 10³ CFU/g, respectively. The kefir butter had good acceptance, achieving an overall score of 7.6 and a purchase intent score of 4.4. The butter obtained from cream fermented with kefir demonstrated good acceptance and a high LAB count, indicating functional and probiotic properties. However, improvements are needed to reduce moisture and acidity, which could enhance both shelf life and consumer acceptance. The use of kefir as a fermenting culture in dairy products, such as butter, represents a promising innovation, allowing the incorporation of viable probiotic microorganisms into diverse food matrices and expanding probiotic consumption options beyond traditional yogurts and fermented beverages.